Comparison of ibrutinib and idelalisib plus rituximab in real‐life relapsed/resistant chronic lymphocytic leukemia cases. (28th January 2021) - Morabito, Fortunato; Tripepi, Giovanni; Del Poeta, Giovanni; Mauro, Francesca Romana; Reda, Gianluigi; Sportoletti, Paolo; Laurenti, Luca; Coscia, Marta; Herishanu, Yair; Bossio, Sabrina; Varettoni, Marzia; Murru, Roberta; et al.
Abstract: Objectives: To compare the capacity of ibrutinib (IB) and idelalisib‐rituximab (IDELA‐R) of prolonging overall survival (OS) as in CLL patients, previously treated with chemotherapy only. Methods: A real‐life cohort of 675 cases has been identified and investigated in the database of the groups participating in the study. Results: At an unadjusted univariate analysis, a significant death risk reduction was observed favoring IB (IDELA‐R vs IB HR = 0.5, 95% CI = 0.36‐0.71) although with some limitations due to the non‐randomized and retrospective nature of the study and to the lower number of patients in the IDELA‐R group (112 cases) related to the current prescribing practice. To overcome the potential problem of confounding by indication, we adjusted the association between the type of therapy and mortality for all variables significantly associated with OS at Cox univariate analysis. Furthermore, those variables, differently distributed between the two study groups, were introduced into the multivariate Cox model to improve the effectiveness of the analysis. By introducing all these variables into the multiple Cox regression model, we confirmed the protective effect of IB vs IDELA‐R (HR = 0.67, 95% CI = 0.45‐0.98, P  = .04) independent of potential confounders. Conclusions: Although our analysis presents some constraints, that is, the unavailability of additional potential confounders, and the retrospective nature of the study, this observation may be of help for the daily clinical practice, particularly in the absence of randomized trials comparing the two schedules.